Penerapan Sistem Akuntansi Pada PT.Segi Muda Bertiga - Ranti Widia; Devina Dewi Aryanto; Tiara Fauzan Setiawan; Vitara Pier; Putri Indah Sakhira; O. Feriyanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development of modern companies often leads to overlapping functions between departments, such as the dualism of functions between Human Resources (HR) and financial accounting. This creates serious challenges in resource management and accounting that can impact the overall performance of the organization. Issues faced include overly simplistic financial recording due to HR's lack of expertise in accounting, as well as the risk of errors and data inaccuracies. This research aims to provide in-depth insights into the impact of HR and financial accounting dualism at PT. Segi Muda Bertiga and identify solutions to enhance the efficiency and accuracy of resource and financial management. The research method employs a qualitative approach, analyzing five main theoretical studies, including cash sales accounting systems, payroll and wage analysis, cash receipts, inventory, and purchases. Data is gathered through interviews, literature reviews, and document analysis.